Comparative efficacy of immunomodulators and sensitive antibiotic on endometrial histopathology in endometritis in crossbred cows - PRASAD, J K; SAXENA, M S; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to evaluate the efficacy ofimmunomodulators (E.coli LPS & oyster glycogen) and sensitive antibiotic on endometrial histopathology used for treatment of endometritis in crossbred cows. Forty eight cows tested positive for endometritis on the basis of appearance and white side test were randomly divided into 4 groups with 12 cows in each group. In group A, I 00 μg of£. coli LPS once, in group B, 500 mg oyster glycogen (OG) once, in group C, most sensitive antibiotic i.e. enrofloxacin was infused intrauterine for 3 consecutive days and in group D, 20 ml PBS was infused once which served as control. Endometrial biopsies were collected at O hour i.e. before treatment and at 72 hours after treatment from all the groups for histopathological study. The incidence of acute/mild type of endometritis was significantly (P<0.01) higher than subacute and chronic endometritis. A significant reduction in the cases of endometritis was observed after treatment with LPS (P<0.01) and OG (P<0.05). Treatment with most sensitive antibiotic also reduced the cases of endometritis but this reduction was non significant. Infusion of LPS and OG reduced the cases of denuded epithelium and completely cured pseudostratification of epithelium. Increased infiltration of PMN cells and mononuclear cells in the endometrial epithelium after PLS and OG infusion are indicative of increase in the degree UDM. Infusion of LPS caused complete recovery of the different types of pathological conditions of the endometrial glands except one case of cystic dilatation. Infusion ofOG also led to significant recovery except 3 chronic cases of endometritis. All lymphoid follicles were also cleared following OG infusion probably because of its immunomodulatory effect. Infusion ofantibiotic intrauterine resulted in to 25% increase in histopathological changes associated with endometrial epithelium. In untreated control group, histological studies revealed no change in endometrial epithelium as compared to before treatment. It was revealed that LPS and OG significantly cured all types of endometritis and is better therapy for endometritis than antibiotic. Repeated intervention of endometrium for intrauterine infusion of antibiotic markedly enhanced the condition of mild endometritis.